Perspectives of Equality: Work, Women, and Family in the Nordic Countries and EU - Mahon, Rianne (Labour / Le Travail, 2002)
The article reviews the book, "Perspectives of Equality: Work, Women, and Family in the Nordic Countries and EU," edited by Laura Kalliomaa-Puha.